The Congenital Cardiology Cloud – optimizing long-term care by connecting ambulatory and hospital medical attendance via telemedicine - Rottermann, Kathrin; Doll, Ulrike; Pfenning, Simon; Reichenbach, Marc; Fey, Dietmar; Dobler, Alexander; Siauw, Céline; Reif, Fabian; Gnibl, Julia; Cesnjevar, Robert; Dittrich, Sven (Klinische Pädiatrie, 2023)
Background Patients with complex congenital heart disease frequently undergo a life-long ambulatory therapy with the need for repeated hospital interventions. To optimize this manifold interplay, we designed and implemented a tele-medical service, the Congenital Cardiology Cloud (CCC). This study aims to analyse the requirements for its implementation through the comprehensive assessment of design, installation and impact on patient´s care.Methods CCC’s development comprised the analysis of historically raised admission and discharge management and the definition of technical and organizational requirements. Elaboration of procedural flow charts, description of data formats and technical processes as well as distribution of patient structure formed part of this process.Results Analysis of existing workflows uncovered a need for the rebuilding of admission and discharge process and decision making for further treatment. The CCC reduces conference-meetings in general and repetitive meetings up to less than a third. Real-time dispatch of discharge documents guarantees an instantaneous access to patient-related data. Comparative analyses show a more complex patient group to be involved in tele-medical services.Conclusions The CCC enables the sharing of complex clinical information by overcoming sectoral barriers and improves mutual patient advice. Implementation of a tele-medical network requires willingness, perseverance and professional engagement. Future application analysis and possible introduction of refinancing concepts will show its long-term feasibility.
Keywords: telemedicine; telecardiology; congenital heart disease; cloud; data security; pediatric cardiology